2000
DOI: 10.1016/s0378-1097(00)00059-8
|View full text |Cite
|
Sign up to set email alerts
|

Production of N-acyl-?-homoserine lactones by P. aeruginosa isolates from chronic lung infections associated with cystic fibrosis

Abstract: The N-acyl-L-homoserine lactones (AHLs) produced by sequential Pseudomonas aeruginosa isolates from chronically infected patients with cystic fibrosis were analyzed by thin-layer chromatography. It is demonstrated that both the amounts and the types of molecules synthesized by isolates from patients who were monitored over periods of up to 11 years do not change significantly during chronic colonization. However, in the case of a patient who became co-infected with an AHL-producing Burkholderia cepacia strain … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
59
0

Year Published

2001
2001
2019
2019

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 40 publications
(62 citation statements)
references
References 15 publications
3
59
0
Order By: Relevance
“…In a first step to assess the possibility of AHL-mediated intergeneric signalling between P. aeruginosa and B. cepacia we determined the AHL profiles of bacterial isolates from one CF patient who became co-infected with B. cepacia (Geisenberger et al, 2000). P. aeruginosa SH1, a strain that was isolated from the patient prior to co-infection with B. cepacia, produced large amounts of AHL molecules.…”
Section: Ahl Profiles Of Strains Used In This Studymentioning
confidence: 99%
See 4 more Smart Citations
“…In a first step to assess the possibility of AHL-mediated intergeneric signalling between P. aeruginosa and B. cepacia we determined the AHL profiles of bacterial isolates from one CF patient who became co-infected with B. cepacia (Geisenberger et al, 2000). P. aeruginosa SH1, a strain that was isolated from the patient prior to co-infection with B. cepacia, produced large amounts of AHL molecules.…”
Section: Ahl Profiles Of Strains Used In This Studymentioning
confidence: 99%
“…On the basis of their mobilities (R F values) and by including appropriate reference compounds it was concluded that these molecules represent 3-oxo-C12-HSL, 3-oxo-C8-HSL, 3-oxo-C14-HSL, C6-HSL and C8-HSL ( Fig. 2 ; Geisenberger et al, 2000). As a control we also included the well-characterized P. aeruginosa strain PAO1 in this analysis.…”
Section: Ahl Profiles Of Strains Used In This Studymentioning
confidence: 99%
See 3 more Smart Citations